Obtaining a lytic bacteriophage suitable for use in phage therapy against Clostridioides difficile infection - Kerr, Sarah (2023)
Clostridioides difficile is the leading cause of hospital-acquired and antibiotic-associated diarrhoea in the developed world. More effective countermeasures are required. Phage therapy, based on lytic bacteriophage, is a particularly attractive option. To date, however, all described C. difficile phages have proven to be temperate.